Bangladesh : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2001 Article IV Consultation highlights that Bangladesh's economy became progressively more fragile after the mid-1990s owing to a persistent pursuit of expansionary fiscal and monetary policies along with slow progress on needed structural reforms, especially in the banking and state-owned enterprises (SOEs) sectors. Rising credit demands of the government, the SOEs, and the private sector were readily accommodated by monetary policy. These growing domestic imbalances were reflected in pressures in the foreign exchange market and by a marked decline in international reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet